2012
DOI: 10.4103/1463-1741.99861
|View full text |Cite
|
Sign up to set email alerts
|

Estimating occupant satisfaction of HVAC system noise using quality assessment index

Abstract: Noise may be defined as any unwanted sound. Sound becomes noise when it is too loud, unexpected, uncontrolled, happens at the wrong time, contains unwanted pure tones or unpleasant. In addition to being annoying, loud noise can cause hearing loss, and, depending on other factors, can affect stress level, sleep patterns and heart rate. The primary object for determining subjective estimations of loudness is to present sounds to a sample of listeners under controlled conditions. In heating, ventilation and air c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…After reviewing similar studies (Albuainain et al, 2021;Zhang et al, 2018), the authors observed that occupants might be oblivious to maintenance issues in a facility. Besides, certain studies have investigated building performance evaluation and postoccupancy evaluation, which addressed HVAC systems in health-care facilities (Brambilla and Capolongo, 2019;Dilrukshi et al, 2014;Forouharmajd et al, 2012). However, these studies are limited and mainly focus on certain HVAC performance elements such as noise.…”
Section: Literature Reviewmentioning
confidence: 99%
“…After reviewing similar studies (Albuainain et al, 2021;Zhang et al, 2018), the authors observed that occupants might be oblivious to maintenance issues in a facility. Besides, certain studies have investigated building performance evaluation and postoccupancy evaluation, which addressed HVAC systems in health-care facilities (Brambilla and Capolongo, 2019;Dilrukshi et al, 2014;Forouharmajd et al, 2012). However, these studies are limited and mainly focus on certain HVAC performance elements such as noise.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The influence of the HVAC system is vital, because it can contribute to reducing the energy consumption of a building and preserving appropriate indoor air quality [14]. In addition, the important criteria of choosing an HVAC system have to be considered, such as a low noise level in the building [15]. Furthermore, the ASHRAE standards give importance to the criterion of durability.…”
Section: Hvac System Evaluation Criteriamentioning
confidence: 99%
“…Heating options based on heat pumps Carrier [41] C5: Sound rating level System noise Farhad et al [15] C6: Air replenishment Use of fresh air in HVAC system ASHRAE standard 62.1 [42] In addition to criteria related to evaluating HVAC quality, according to previous studies, other criteria in the HVAC selection process are related to aesthetics, buildability, sustainability, and durability [16,17]. Eight HVAC selection criteria associated with system quality are described in Table 5.…”
Section: Hvac System Alternativesmentioning
confidence: 99%
See 1 more Smart Citation
“…The unpleasant sound or noise is a factor that influences noise pollution (e.g., the noise produced by airplanes, cars, industrial process machinery, and sound systems), and therefore, devices like transformers can affect human beings [1,2]. In electrical transformers, noise can be caused by different physical effects, such as the pile-up of magnetic sheets that form the core, the winding, and the air forced cooling systems [3,4], which combined may provoke really high levels of noise that would exceed the limits established by national and international standards.…”
Section: Introductionmentioning
confidence: 99%